1984
DOI: 10.1177/00220345840630061701
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Levels in Dentin after Iontophoresis of 2% NaF

Abstract: The fluoride in successive layers of dentin (from 3-6 micron were removed per etch) has been measured following topical or iontophoretic application of 2% aqueous sodium fluoride to coronal exposed dentin of freshly extracted human third molar teeth. The fluoride contents of the topical and iontophoresed first etches were, respectively, 12 and 22-31 times greater than that of control (untreated) teeth. Similarly, the fourth etches were 12 and 50-70 times greater, and the seventh (last sampled) etches were 5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The findings support those obtained by previous studies. 14,15,30,31 However, the remineralization effect of iontophoresis NaF was significantly lower than that of APF gel. Recently, APF gel has become popular among dental practitioners and is known to be an effective method for reducing the incidence of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…The findings support those obtained by previous studies. 14,15,30,31 However, the remineralization effect of iontophoresis NaF was significantly lower than that of APF gel. Recently, APF gel has become popular among dental practitioners and is known to be an effective method for reducing the incidence of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…These ions chemically react with free calcium ions, in particular from the dentinal fluid, forming acid-resistant calcium fluoride that occludes the tubules to varying extents. 28 There is a direct relationship between the frequency and duration of fluoride ionophoresis treatment and the size, form and depth of occluding-particle penetration in the tubules. 29 SEM photomicrographs showed that treatment of the specimens with 6% citric acid for 2 min in an ultrasonic bath effectively removed the dentin smear layer, creating a smooth surface with exposure of dentinal tubule orifices (Fig.…”
Section: 2mentioning
confidence: 99%
“…NaF is used widely, yielding predictable positive results in many cases. 13 Additionally, iontophoresis has been shown to increase the uptake of F. 14 A novel treatment has been developed to treat CDH. In NovaMin Ò (NM) (Denshield, NovaMin Ò Technology, FL), the active ingredient is a bioactive glass that has been ground into a fine particulate with a median size of < 20 lm, composed of Ca, P, Na, Si, and O.…”
Section: Introductionmentioning
confidence: 99%